2021
DOI: 10.1186/s13075-021-02417-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment persistence of biologics among patients with psoriatic arthritis

Abstract: Background Persistence of biologic therapy in psoriatic arthritis (PsA) patients is an important factor in individualized patient treatment planning and healthcare policy and guideline development. Objective To estimate the persistence of biologic agents prescribed to PsA patients in a real-life setting as well as factors associated with improved biologic drug survival in these patients. Methods Patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 34 publications
5
29
2
4
Order By: Relevance
“…Other studies, evaluating the same outcome, estimated approximately 47% of PsA patients, from the UK, remained on their initial TNFi therapy after 5 years and low persistence of 32% after 5 years of follow-up on PsA patients in Germany, while no differences among TNFi were observed [20][21][22]. Recently, none of the TNFi agents was found to be more persistent than others as first-line therapy, while secukinumab was found to be superior to other biologics when indicated as second-line therapy [23]. However, data from Slovenia showed a better persistence of GLM compared to other TNFis in bDMARD-experienced AS and PsA patients [19].…”
Section: Discussionmentioning
confidence: 93%
“…Other studies, evaluating the same outcome, estimated approximately 47% of PsA patients, from the UK, remained on their initial TNFi therapy after 5 years and low persistence of 32% after 5 years of follow-up on PsA patients in Germany, while no differences among TNFi were observed [20][21][22]. Recently, none of the TNFi agents was found to be more persistent than others as first-line therapy, while secukinumab was found to be superior to other biologics when indicated as second-line therapy [23]. However, data from Slovenia showed a better persistence of GLM compared to other TNFis in bDMARD-experienced AS and PsA patients [19].…”
Section: Discussionmentioning
confidence: 93%
“…32 A claims-based cohort study with 1,558 PsA patients found that secukinumab initiators were more adherent than initiators of TNF inhibitors, 28 and a study based on a large health care provider database concluded that secukinumab was superior to adalimumab, infliximab, and ustekinumab, only when they were indicated as second-line therapy. 33 In contrast, registry-based studies such as PSOriasis Longitudinal Assessment and Registry (PSOLAR), British Association of Dermatologists Biologic Interventions Register (BADBIR), and a population study using Swedish administrative registries reported a better drug survival of ustekinumab compared with TNF inhibitors among PsA or psoriasis patients. [34][35][36] Nevertheless, data in these studies and in our study are limited to further identify specific reasons for treatment discontinuation or switching.…”
Section: Discussionmentioning
confidence: 99%
“…До начала эры биологической терапии ПсА арсенал ревматологов был представлен, главным образом, стандартными синтетическими базисными противовспалительными препаратами (сБПВП), которые часто применяли в комбинации с локальным введением глюкокортикоидов. В качестве «золотого стандарта» первой линии терапии как ранее, так и в современных рекомендациях рассматривают метотрексат -иммуносупрессивный препарат с выраженной противовоспалительной активностью, влияющий на активность дигидрофолатредуктазы и ингибирующий пролиферацию иммунных клеток [20].…”
Section: лечение псориатического артритаunclassified